10.61533 TINJAUAN PENGARUH KEPEMIMPINAN HEROIK DAN ORGANISASI PEMBELAJARAN TERHADAP PRESTASI KERJA PADA ANGGOTA GMNI BABEL - Fukita, Titania; Ruben Manullang, Rizal; Tri Setyo Mulyani, Hendarti (STIE IBEK Pangkalpinang, 2024)
The purpose of this research is to identify the effects of Heroic Leadership and Learning Organization to GMNI members work performance. This research use a quantitative descriptive approach as its primary data. Subjects within this research involves 72 active GMNI members as respondents, and also using Likert scale questionnaire. The research also used multilinear regression analysis as its data analysis technique which is then processed using University of Amsterdam’s JASP (Jeffreys’s Amazing Statistics Program). The results of this research suggest: (1) Heroic leadership partially affects work performace with a significancy value of 0,0001 < 0,05 and tvalue of 14,521 > ttable 1,667. (2) Learning organization had no partial effect to work performance with a significancy value of 0,046 < 0,05 and tvalue 0,550 < ttable 1,667. (3) Heroic leadership and learning organization simultaneously affects work performance, with a significancy value of 0,001 < 0,05 and fvalue 105,496 > ftabel 3,13